HUBUNGAN KEBIJAKAN PUBLIK TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TENGAH - Muhammad Arif Rakhman (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
Public policy has a function as supporting governance. Public policy factors include investment, labor, and government spending. In this study using the panel data regression analysis method with the CEM (Common Effect Model), FEM (Fixed Effect Model), RAM (Random Effect Model) approach. From this study partially output obtained Investment regression coefficient value -0.002313, Labor regression coefficient value of 0.109465 and p-value of 0.0859, and government spending regression coefficient value of 1.036837 and p-value of 0.0000 then, the investment coefficient value has an influence negative is not significant to Economic Growth, while the value of the coefficient of labor and the coefficient of government spending has a significant level of Economic Growth.